STUDY OF SUPERIOR COMMODITIES AND ITS SPATIAL DISTRIBUTION IN BANGKA BELITUNG ARCHIPELAGO PROVINCES - Riswan Septriayadi Sianturi; Luthfi Muta'ali (Faculty of Geography, Universitas Gadjah Mada, 2010)
ABSTRACTEconomic development in decentralization era, presumably, will not besustainable if only supported by non-renewable resources. Then, local governmentneed to changefrom mining to non-mining based economic development. The nonrenewableresources themselves are used as capital in the transformation process.In supporting these endeavours, study of superior commodities in Bangka BelitungArchipelago Provinces is need to be conducted as efforts to increase society'swelfare or other stakeholders post decreasing of tinproduction this province.